Adsorption of size-polydisperse particles on sinusoidally corrugated surfaces. Issue 6 (13th April 2018) - Schoch, Phillip K.; Genzer, Jan
Abstract: We use adhesion model based on Monte Carlo computer simulation to study adsorption of core-shell spherical particles of polydisperse sizes onto sinusoidally corrugated substrates with predefined amplitude (A) and wavelength ( λ ). The core-shell particles comprise a hard inner core and an adhesive shell that mediates interaction with the substrate lattice elements. The probability distribution of particle sizes (diameters) is determined by either a single normal distribution function (Dmean  = 20) of standard deviation 0–8 (0–40% of Dmean ) or a bimodal distribution function constructed by adding two normal distributions of differing mean values. Using comparisons of these surface textures to flat substrates the surface texture reduces adhesion strength by up to ~40% for feature height 20 at λ /Dmean  = 0.5 depending on the standard deviation. In systems featuring bimodal particle size distributions we observe that for mean particle size ratio (Dmean B /Dmean A ) of 2 surface texture continues to reduce the adhesion strength of particles by ~40–50% for some combinations of A and λ when compared to flat analogues. However, at mean particle size ratio of 4, the surfaces tested no longer reduce particle adsorption significantly. This suggests that when particle sizes are far apart a second texture is needed to act against the smaller particles.